PENGARUH FINANCIAL LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MARLINA WIDIYANTI; FRISKA DWI ELFINA (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This research is aimed to investigate the influence of financial leverage which proxied by the Debt to Asset Ratio (DAR), the Debt to Equity Ratio (DER), and the Long Term Debt to Equity Ratio (LDER) on Profitability which proxied by the Return on Assets (ROA) in the Automotive and Components sub sector company listed in Indonesia Stock Exchange period 2010-2013. The population in this research is 12 companies of Automotive and Components sub sector. Sensus technique is employed and found 12 companies are selected for the research sample. The result shows that partially, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long Term Debt to Equity Ratio (LDER) had negative but not significant influence on Return on Assets (ROA). Simultaneously, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long Term Debt to Equity Ratio (LDER) did not have significant influence on Return on Assets (ROA). The coefficient of determination is11,4%, it means that financial leverage variables are be able to explain profitability variable as much as 11,4%, and the rest of 88,6% explained by other variables. The implications of this research is the manager may consider the proportion of debt and for investors is useful as consideration in making investment. Due to limited of this research, it is recommended to add other sectors, extend the period of research and use more of other independent variables.